Implementasi Metode Tadhadh (Antonim) dalam Pemerolehan Kosakata Bahasa Arab Melalui Hiwar Berbahasa Arab - Widodo, Joko; Putra, Sudarmadi; Budiriyanto, Anis; Winanto, Edy; Romadhon, Farkhan Nur (Nusantara: Jurnal Pendidikan Indonesia, 2023)
This study aims to describe the implementation of the Tadhad (antonym) method in acquiring Arabic vocabulary and analyze students' understanding of vocabulary acquired through the Tadhad method in Arabic language learning for 10th-grade students of Class A at SMA ISLAM 1 Surakarta. The study employs a qualitative approach using observation, interviews, and document analysis to obtain in-depth data related to students' learning experiences and vocabulary acquisition progress through the antonym method. The findings indicate that the application of the Tadhad method in Arabic vocabulary learning is effective in enhancing students' understanding of new word meanings due to the logical associations between antonyms, improving vocabulary comprehension through semantic relationships and real-world contexts, and helping students gain confidence in speaking Arabic. However, the implementation of this method requires additional strategies, such as the use of contextual examples and repeated practice, to maximize learning outcomes.